Body fat and stroke: unmasking the hazards of overweight and obesity. Issue 3 (June 1995) - Shinton, R; Sagar, G; Beevers, G
Abstract : STUDY OBJECTIVE–It has been frequently noted that overweight and obesity have a stronger relationship to hypertension and diabetes mellitus than to the risk of stroke. The reason for this observation has not been clear. This study aimed to examine the lifelong relation between body fat and stroke to shed light on why the public health risks of overweight and obesity have tended to be obscured in previous epidemiological studies. DESIGN–Case-control study. SETTING–Eleven general practices in west Birmingham. PARTICIPANTS–Altogether 125 men and women who had just had their first stroke and were aged 35-74 years and 198 controls frequency matched for age and sex were recruited over 24 months during 1988-90. MAIN RESULTS–Those in both the thinnest and fattest quartiles of subscapular skinfold thickness were at increased risk of stroke compared with those in the middle quartiles (age adjusted odds ratios 2.12 (95% confidence interval (CI) 1.2, 3.9) and 2.08 (1.1, 3.8) respectively). When lifelong maximum reported body mass index was assessed the hazards of obesity but not leanness were seen (odds ratio for the highest versus the lowest quartile were–age adjusted, 1.54 (0.8, 3.0) and multiple risk factor adjusted, 2.25 (1.1, 4.5). This lifelong pattern of risk seemed to be established early, the odds ratios for the highest versus the lowest quartile of reported body mass index aged 21 years were–age adjusted, 2.18 (1.1, 4.4) and multiple risk factor adjusted 2.13 (1.1, 4.2). The risks of both maximum reported body mass index and reported body mass index aged 21 years were more clear in those who had never smoked cigarettes (test for trend in odds ratio, p = 0.009 and p = 0.02 respectively). CONCLUSIONS–Potentially important risks of excessive body fat for stroke can be obscured by both a history of cigarette smoking and thinness associated with deteriorating health. The results seem to explain why excess body fat has previously been consistently related to hypertension and diabetes mellitus but less consistently to stroke. Avoiding overweight and obesity during adult life offers protection against stroke.